“If”, by Rudyard Kipling - an intermedial production - Ignácio da Costa, Érica; Saber de Mello, Ines (Lumina - Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal de Juiz de Fora, 2015)
This paper aims to build a theoretical support in intermediality studies to a doc-poetry creation on the poem If by Rudyard Kipling. Despite of being short, If is a poem that offers multiple interpretations because it suggests cycles and growth, it stimulates the creation of images. This poem selection went through our perception of the central presence of the embodiment, and therefore it is quite translatable into body and image to create a new media. Its interpretation by the language of doc-poetry becomes a mean of establishing new creative ways of interpreting the poem. As a transcreation process, the choreography’s composition procedures have considered the original’s poem structure, and also the body’s perception. The creative ability of source text transformation into a different media can expand its interpretative possibilities. In this case, cinema, dance/body and poetry were used as media for creating a new artistic expression, which we not permanently term doc-poetry. The choreographic body and a mix of technicalities reveal a potentiality to express beyond the speeches. When crossing theory and practice it is possible to think and test the body in other media and also as a new media itself. Therefore, working the body and the film as artistic and interpretative possibilities of written text is a way of seeing new potentials when reading. Therefore, the research challenge was to work the poem If by the bias of embodiment, where the choreography turns theory, the body, a new media, while dance and cinema, a way of reading poetry.